Diversifikasi Dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Siti Chaerunisa Prastiani; Khoirunnisa Azzahra (Jurnal Riset Akuntansi Politala, 2026)
This study aims to obtain empirical evidence regarding the effect of Diversification and Company Size on Company Financial Performance. The data used in this study are secondary data in the form of financial reports from each company selected as the research sample. The population of this study is the Consumer Non-Cyclicals Sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2020–2024, totaling 123 companies. Sample selection in this study used the Purposive Sampling technique, yielding 21 sample companies (105 total observations). This type of research is quantitative descriptive research. The data analysis method used is Panel Data Regression using Eviews version 13, through the stages of determining the appropriate panel data model (Chow test, Hausman test, and Lagrange Multiplier test), Classical Assumption Test, and Hypothesis Testing. The results show that simultaneously, diversification and company size have a significant influence on company performance. Partially, both diversification and company size have a positive and significant effect on the company's financial performance.